Risk Factors Recurrent Respiratory Papilloma (RRP) on Juvenile and Adult Type in Tertiary Hospital, Indonesia - Rizka Fathoni Perdana (Journal of Global Pharma Technology, 2020)
Introduction: Recurrent respiratory papillomatosis (RRP) is the most common benign neoplasm of the larynx among children as a result of HPV infection mainly type 6 and 11. RRP is still a serious problem in which papillomas in the airway cause hoarsness and obstruction as then described as an aggressive form and less aggressive form. Patients undergo multiple surgeries to keep the airway patent and in order to communicate vocally. There are several risk factor that affect on disease aggressivity. That factors include sex, age at diagnosis, papilloma implantation, tracheostomy, number of surgery, and histopathology. Aim: to determine the relationship between risk factors for RRP with the level of aggressiveness in juvenile type and adult type. Method: This research used analytic retrospectively, the data obtained from the medical record of outpatient unit of the otolaryngology-head and neck surgery department. The data obtained in the study are displayed in tables and analyzed statistically using the Chi-Square test. The research sample was taken according total sampling. Result: The statistic test result was indicating the statistical test using Chi-Square results (p